Reviving growth in India - Agrawal, Pradeep (2015)
"Discusses some of the unresolved questions relating to reviving growth in India covering various sectors of the economy"--
Includes bibliographical references and index.
Keywords: Industrial policy -- India; India -- Economic policy; India -- Commercial policy